Optimization of Somatic Embryogenesis Protocol for Locally Adapted Eggplant (Solanum melongena L.) Varieties in Bangladesh (Plant Tissue Culture and Biotechnology, 2016)
Five eggplant cultivars were cultured on MS supplemented with 0.5 mg/l 2,4?D, resulting in the development of embryogenic calli. When the calli were subcultured onto growth regulator free MS, BARI Begun?4 produced the highest number of embryos (64) per explant followed by BARI Begun?1 (57). Later both the superior varieties in terms of embryo production were cultured on MS having 0.5, 1.0, 1.5 and 2.0 mg/l 2,4?D along with a control. BARI Begun?4 produced the highest number of embryos (67) on MS supplemented with 1.0 mg/l 2,4?D which was closely followed by BARI Begun?1 (62). Regenerated plantlets were successfully established in soil following acclimation.Plant Tissue Cult. & Biotech. 26(1): 77-83, 2016 (June)